Effects of Increasing Standardized Ileal Digestible Valine:Lysine Ratios on the Growth Performance of 50 to 80 lb Pigs - Samantha A. Swanson; Jason C. Woodworth; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Katelyn N. Gaffield; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 351 pigs (DNA 600 × 241; initially 47.1 ± 0.77 lb) were used in a 21-d experiment to determine the effects of increasing standardized ileal digestible (SID) Val:Lys ratio in 50 to 80 lb pigs. There were 12 replications per treatment with five pigs per pen. Pens of pigs were randomly assigned to one of six corn-soybean meal-based dietary treatments with SID Val:Lys ratios of 60, 63, 66, 69, 72, and 75%. A basal diet was formulated with the lowest SID Val:Lys ratio and L-valine was added to create the diet with the highest Val:Lys ratio. The high and low diets were then blended to create the intermediate diets. On d 0, 10, and 21, pigs were weighed to determine ADG, ADFI, and F/G. Blood was drawn on d 10 for plasma urea nitrogen (PUN) analysis. From d 0 to 10, BW, ADG and F/G improved (linear, P < 0.05) as SID Val:Lys ratio increased, but with little improvement past a 72% Val:Lys ratio. No differences were observed from d 10 to 20 (P > 0.10). Similar to d 0 to 10, the overall F/G improved (linear, P = 0.012) as Val:Lys ratio increased but with little improvement past 72% Val:Lys ratio. As Val:Lys ratio increased, there was an increase in PUN concentration (linear, P = 0.029). Valine intake grams per day and Val intake per kg of gain increased (linear, P < 0.001) as Val:Lys ratio increased. Lysine intake per kg of gain decreased (linear P = 0.029) as the Val:Lys ratio increased. Broken-line analysis indicated overall feed efficiency improved with increasing Val:Lys ratio with the breakpoint at a 69% SID Val:Lys ratio. The results of this study suggest that a 69 to 72% SID Val:Lys ratio may be ideal for 50 to 80 lb pigs.
Keywords: amino acid; growing pig; lysine; valine